Kepemimpinan: Suatu Tinjauan Manajemen Sumber Daya Manusia - Heryanto, Januar (Bina Nusantara University, 2005)
Leadership qualities might naturally â€œinbornâ€ to some people, but for someÂ others have to make efforts to grow the leadership qualities in themselves. Itâ€™s wellknownÂ as a â€œformed-leadersâ€, leadership that grows through examples and experiences. Leaders should have a vision to see the future from the distance. They dream is not onlyÂ about what can be happened to day, but also about what will happen in next year, in next decade, even in next generation.Â